Novel p-dopant toward highly efficient and stable perovskite solar cells. Issue 10 (30th July 2018) - Seo, Ji-Youn; Kim, Hui-Seon; Akin, Seckin; Stojanovic, Marko; Simon, Elfriede; Fleischer, Maximilian; Hagfeldt, Anders; Zakeeruddin, Shaik M.; Grätzel, Michael
Abstract : Zn-TFSI2 is introduced as a powerful p-dopant for spiro-MeOTAD in perovskite solar cells which not only outperforms Li-TFSI but also achieves outstanding long term stability. Abstract : Li-TFSI is the most common p-dopant for the hole conductor spiro-MeOTAD in the normal structure (n–i–p) of perovskite solar cells (PSCs), which consistently yield the highest power conversion efficiency (PCE) albeit at the risk of lower long-term operational stability. Here we successfully replace conventional Li-TFSI with Zn-TFSI2, which not only acts as a highly effective p-dopant but also enhances considerably both the photovoltaic performance and long-term stability. The incorporation of Zn-TFSI2 as a dopant for spiro-MeOTAD leads to an increase by one order in the hole mobility compared to Li-TFSI from 3.78 × 10 −3 cm 2 V −1 s −1 to 3.83 × 10 −2 cm 2 V −1 s −1 . Furthermore, the device with Zn-TFSI2 showed an 80 mV higher built-in voltage and a bigger recombination resistance than the one with Li-TFSI, which were responsible for the striking increase in both the open-circuit voltage and fill factor, leading to a stabilized PCE of 22.0% for the best cells. Remarkably, the device employing Zn-TFSI2 demonstrated superb photo-stability, showing even a 2% increase in the PCE after 600 h light soaking at the maximum power point (mpp) under full sun, while the PCE of the device with Li-TFSI decreased by 20% under the same conditions. Similarly, the device with Zn-TFSI2 showed better operational stability at 50 °C resulting in a 21% decrease in the PCE after 100 h aging at the mpp under full sun while the Li-TFSI based one showed a 55% decrease. Moreover, the Zn-TFSI2 based device was capable of effectively resisting humidity compared to the one based on Li-TFSI from shelf stability monitoring (R.H. ≥ 40%) in the dark.